Soluble immune checkpoints as correlates for HIV persistence and T cell function in people with HIV on antiretroviral therapy - Chiu, Chris Y.; Schou, Maya D.; McMahon, James H.; Deeks, Steven G.; Fromentin, Rémi; Chomont, Nicolas; Wykes, Michelle N.; Rasmussen, Thomas A.; Lewin, Sharon R. (Frontiers in Immunology, 2023)
In people with HIV (PWH) both off and on antiretroviral therapy (ART), the expression of immune checkpoint (IC) proteins is elevated on the surface of total and HIV-specific T-cells, indicating T-cell exhaustion. Soluble IC proteins and their ligands can also be detected in plasma, but have not been systematically examined in PWH. Since T-cell exhaustion is associated with HIV persistence on ART, we aimed to determine whether soluble ICs correlated with cellular expression of ICs, markers of the HIV reservoir and HIV-specific immunity in PWH on ART. We used multiplex bead-based immunoassay to quantify soluble programmed cell death protein 1 (PD-1), cytotoxic T-lymphocyteassociated protein 4 (CTLA-4), lymphocyte activation gene-3 (LAG-3), T cell immunoglobulin domain and mucin domain 3 (TIM-3), PD-1 Ligand 1 (PD-L1) and PD-1 Ligand 2 (PD-L2) in plasma from PWH off ART (n=20), on suppressive ART (n=75) and uninfected controls (n=20). We also quantified expression of membrane-bound IC and frequencies of functional T-cells to Gag and Nef peptide stimulation on CD4+ and CD8+ T-cells using flow cytometry. The HIV reservoir was quantified in circulating CD4+ T-cells using qPCR for total and integrated HIV DNA, cell-associated unspliced HIV RNA and 2LTR circles. Soluble (s) PD-L2 level was higher in PWH off and on ART compared to uninfected controls. Higher levels of sPD-L2 correlated with lower levels of HIV total DNA and higher frequencies of gag-specific CD8+ T-cells expressing CD107a, IFN 𝛄 or TNFα. In contrast, the concentration of sLAG-3 was similar in uninfected individuals and PWH on ART, but was significantly elevated in PWH off ART. Higher levels of sLAG-3 correlated with higher levels of HIV total and integrated DNA, and lower frequency of gag-specific CD4+ T cells expressing CD107a. Similar to sLAG-3, levels of sPD-1 were elevated in PWH off ART and normalized in PWH on ART. sPD-1 was positively correlated with the frequency of gag-specific CD4+ T cells expressing TNF-a and the expression of membrane-bound PD-1 on total CD8+ T-cells in PWH on ART. Plasma soluble IC could be potential biomarkers of HIV reservoir and HIV-specific T-cell function in large population-based studies of PWH on ART.